From trade preferences to trade facilitation: Taking stock of the issues - Maria Persson (Kiel Institute for the World Economy (IfW), 2011)
The objective of the paper is to explore and give an overview of two central policy alternatives to improve the integration between the European Union and developing countries by removing barriers to trade: trade preferences and trade facilitation. After reviewing the relevant literatures and discussing the issues which constitute problems or opportunities for practitioners and researchers in both areas, the paper concludes that while at least some trade preferences actually have been less of a failure than their reputation suggests, trade facilitation is a far more promising policy option for the future.
Keywords: F10; F13; F15; 330; Trade preferences; Trade Facilitation; European Union; Developing Countries; Außenhandelsliberalisierung; Außenwirtschaftspolitik; Internationale Handelspolitik; Außenhandelseffekt; Außenhandelspräferenz; Außenhandelsgewinn; Handelsabkommen; Entwicklungsländer; EU-Staaten